2018
DOI: 10.1016/j.jacbts.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Increases Cardiac Energy Production in Diabetes

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
137
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(174 citation statements)
references
References 37 publications
9
137
1
Order By: Relevance
“…Various hypotheses have been advanced to explain these effects, for example, the increased ketone concentrations found with SGLT2 inhibitor use. Since ketones are optimal substrates for all tissues, including the heart, as they require less oxygen (than FFAs) for oxidation, Ferrannini et al 46 49 Other hypothesized mechanisms include decreased blood pressure, 50 plasma volume, 51 a re-arrangement of myocardial electrolyte handling 52 and many others. None of these, however, has been completely convincing, and the main mechanism(s) promoting the beneficial cardiovascular effects remains unclear.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…Various hypotheses have been advanced to explain these effects, for example, the increased ketone concentrations found with SGLT2 inhibitor use. Since ketones are optimal substrates for all tissues, including the heart, as they require less oxygen (than FFAs) for oxidation, Ferrannini et al 46 49 Other hypothesized mechanisms include decreased blood pressure, 50 plasma volume, 51 a re-arrangement of myocardial electrolyte handling 52 and many others. None of these, however, has been completely convincing, and the main mechanism(s) promoting the beneficial cardiovascular effects remains unclear.…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…In a recent clinical trial, the beneficial effect of sodium glucose co‐transporter‐2 (SGLT2) inhibitor empagliflozin on cardiovascular outcome in patients with diabetes was also thought to be associated with hyperketonemia . However, recent studies showed that despite hyperketonemia, empagliflozin either lowered or did not alter myocardial ketone body utilization in rodent models of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperpolarized 13 C magnetic resonance spectroscopy ( 13 C-MRS) is a powerful technique to study metabolism non-invasively in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations